2018
DOI: 10.1136/bmjoq-2017-000239
|View full text |Cite
|
Sign up to set email alerts
|

Quality improvement of delirium status communication and documentation for intensive care unit patients during daily multidisciplinary rounds

Abstract: Delirium is a key quality metric identified by The Society of Critical Care Medicine for intensive care unit (ICU) patients. If not recognised early, delirium can lead to increased length of stay, hospital and societal costs, ventilator days and risk of mortality. Clinical practice guidelines recommend ICU patients be assessed for delirium at least once per shift. An initial audit at our urban tertiary care hospital in Illinois, USA determined that delirium assessments were only being performed 31% of the time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“… 11 Research has also shown that education and training alone does not ensure knowledge and implementation and that it is suboptimal to sustain screening long term. 12 This provides support for interventions to be multifaceted. Further evidence for multifaceted interventions is supported by research into healthcare change, which found that interventions based on actions such as audit, feedback and reminders and education are more likely to succeed.…”
Section: Discussionmentioning
confidence: 94%
“… 11 Research has also shown that education and training alone does not ensure knowledge and implementation and that it is suboptimal to sustain screening long term. 12 This provides support for interventions to be multifaceted. Further evidence for multifaceted interventions is supported by research into healthcare change, which found that interventions based on actions such as audit, feedback and reminders and education are more likely to succeed.…”
Section: Discussionmentioning
confidence: 94%
“…With the involvement of interprofessional teams at the unit or clinic, we aimed to support this cultural change via adaptation, where appropriate, of the relevant processes. With regard to the overall success of an implementation, the importance of involving all relevant stakeholders, including senior leaders and frontline providers, is supported by the results of other studies and quality improvement projects that use Lean Sigma methodology [37]. Since a cultural change requires time, our chosen time-frame might simply have been too short to show an effect in the expected direction.…”
Section: Discussionmentioning
confidence: 94%
“…A different study confirmed that the use of these educational methods improved the rates of delirium screening by nurses when incorporated into standard daily nursing practice [42]. In addition to education, the standardization of delirium screening documentation and communication of delirium status to clinicians increases delirium screening by dayshift nurses to as high as 93% [43]. An implementation strategy used in another study focused on identifying probable barriers and facilitators for screening via medical staff interviews, resulting in significantly improved screening, from 77% to 92% [44].…”
Section: Implementing Delirium Screening On An Acute Care For the Elderly Unitmentioning
confidence: 90%